2004
DOI: 10.1038/nm1085
|View full text |Cite
|
Sign up to set email alerts
|

Systemic delivery of genes to striated muscles using adeno-associated viral vectors

Abstract: A major obstacle limiting gene therapy for diseases of the heart and skeletal muscles is an inability to deliver genes systemically to muscles of an adult organism. Systemic gene transfer to striated muscles is hampered by the vascular endothelium, which represents a barrier to distribution of vectors via the circulation. Here we show the first evidence of widespread transduction of both cardiac and skeletal muscles in an adult mammal, after a single intravenous administration of recombinant adenoassociated vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
504
1
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 575 publications
(520 citation statements)
references
References 31 publications
12
504
1
3
Order By: Relevance
“…Administration with the vascular endothelial growth factor (VEGF) may facilitate transfer of genetic materials through the endothelium, due to an increase in permeability of the endothelial cell membrane [43]. ECG-triggered sonication may also be effective because ultrasound-based cavitation can be generated precisely at the diastolic phase, when the coronary blood flow is higher than in the systolic phase.…”
Section: Discussionmentioning
confidence: 99%
“…Administration with the vascular endothelial growth factor (VEGF) may facilitate transfer of genetic materials through the endothelium, due to an increase in permeability of the endothelial cell membrane [43]. ECG-triggered sonication may also be effective because ultrasound-based cavitation can be generated precisely at the diastolic phase, when the coronary blood flow is higher than in the systolic phase.…”
Section: Discussionmentioning
confidence: 99%
“…40 Tissue directed in vivo gene transfer has also been attempted by systemic application of pseudotyped AAV6, AAV8 or AAV9 vectors. 38,39,[42][43][44][45] Besides the fact that there is only a limited number of vector serotypes available, by far lower than the variety of potential tissue targets, these serotype-based targeted vectors also have limited or no specificity for the tissue of interest. In congruence with this assumption, our data showed that the library-derived vectors presented here were more specific than AAV serotype 9 (at least with respect to biodistribution of the genomes), which is known to confer efficient transduction of heart tissue.…”
Section: Transgene Expression In Murine Hearts Following Systemic Admmentioning
confidence: 99%
“…Most of these immune responses could be blunted by the use of modified vector backbones (eg by using 'gutted' vectors), muscle-specific promoters (in either Ad or rAAV vectors), or by using ultrapurified vector preparations (eg HPLC purification of lentiviral vectors). 5,6,23,24,43 However, we observed that muscles transduced with the L-CK6-ntsLacZ still showed decreased b-galactosidase activity with increasing time (data not shown), while dystrophin expression from the L-CMV-DH2-R19 vector appeared stable (Figure 2b).…”
Section: Discussionmentioning
confidence: 89%
“…A 571-bp CK6 regulatory cassette derived from the mouse muscle creatine kinase (MCK) gene has previously been shown to maintain muscle-specific activity when tested in Ad and rAAV vectors, which exist as episomes in host cells. 6,23,25 However, since lentiviral vectors integrate into the host genome, we asked whether sequences within the vector genome might interfere with the muscle and differentiation specific activity of the CK6 promoter.…”
Section: Ck6 Regulatory Cassette Maintains Muscle-specific Activity Imentioning
confidence: 99%
See 1 more Smart Citation